Beauty Representation in Scarlett Whitening Advertisement: Roland Barthes' Semiotic Analysis - Setyaningsih, Indah; Palupi, P (Universitas Muhammadiyah Surakarta, 2022)
Purpose: This research delves into one of Indonesia's current popular beauty product advertisements, namely Scarlett Whitening, with the objective of understanding how beauty representation is presented in these ads through Stuart Hall's representation theory and Roland Barthes' semiotic theory. Methodology The study employs a descriptive qualitative approach, analyzed through Roland Barthes' semiotic analysis, which explains the denotative, connotative, and mythical forms of signifiers and signifieds. The study uses three advertisement videos from Scarlett's official Youtube channel, each viewed by over ten million individuals, as samples. The data collection process involved three stages: non-participant observation, documentation, and literature review. Result: The findings indicate that the Scarlett Whitening advertisements attempt to reflect a change in beauty standards, inspired by the white and glowing skin criteria and colorful hairstyles of South Korean and Japanese women in line with current trends. Applications/Originality/Value: Furthermore, the advertisement aims to illustrate that attractive women receive significant social media attention and define beauty through the image of men constructed with the trend of soft masculinity.